Peran Kantor Pertanahan Kota Batu dalam Pelaksanaan Program Percepatan Redistribusi dan Legislasi Tanah di Desa Tulungrejoa - Harisman, Harisman; Imron, Ali (MLJ Merdeka Law Journal, 2024)
Land within the territory of the Republic of Indonesia is one of the main resources, which, in addition to having profound intrinsic value for the Indonesian people, also serves a very strategic function in fulfilling the increasingly diverse and growing needs of the population. The city of Batu still possesses land that is state-owned, inherited from the Colonial Dutch era, which can be utilized for the welfare of Batu's citizens. Given this reality, the author has chosen the title "The Role of the Land Office of Batu City in Implementing the Accelerated Program of Land Redistribution and Legalization in Tulungrejo Village." Based on this title, the issues addressed in this research are: what is the urgency of implementing the Agrarian Reform Program in Batu City, and what are the strategies and steps taken by the Land Office of Batu City in executing the Land Redistribution and Legalization Program in Tulungrejo Village, Batu City. This legal research is based on empirical legal research methods, with a specific systematics and thought process, aiming to study one or several specific legal phenomena. The research findings indicate that, firstly, through the Agrarian Reform Program, Batu City can preserve fertile agricultural lands, provide legal certainty to farmers, increase access to financial resources, reduce poverty levels, and encourage investment in the agricultural sector. Furthermore, through area identification, good socialization, data collection, verification, and issuance of land certificates, the Land Office of Batu City can provide legal certainty to landowners and the local community.